Differences in Self Resilience Between Outstanding and Non-Outstanding Pencak Silat Athletes in Banjarnegara Regency - Pahlewi Asih Mukti; Sulaiman Sulaiman; Heny Setyawati (JUARA : Jurnal Olahraga, 2023)
The objectives of this study are 1) to analyze Self Resilience in outstanding and non-outstanding martial arts male athletes in Banjarnegara Regency, 2) to analyze Self Resilience in outstanding and non-outstanding martial arts female athletes in Banjarnegara Regency, 3) to analyze the differences in Self Resilience in outstanding and non-outstanding martial arts athletes in Banjarnegara Regency. This research uses quantitative methods with a comparative design. The population in this study was athletes in Banjarnegara Regency, athletes with advanced selection representing championships or athletes who had won titles; namely, there were 83 outstanding athletes (BP) and 67 athletes who did not excel (BP TBP). The results of this study: 1) There are differences in self-resilience between outstanding martial arts male athletes and martial arts male athletes who do not excel in Banjarnegara Regency, 2) There is no difference in self-resilience between outstanding martial arts female athletes and martial arts female athletes who do not excel in Banjarnegara Regency, 3) There is a difference in self-resilience between martial arts athletes who excel and martial arts athletes who do not excel in Banjarnegara Regency. Based on the study results, there is a difference in self-resilience between martial arts athletes and those who do not excel in Banjarnegara Regency.